2019
DOI: 10.1111/1468-5973.12274
|View full text |Cite
|
Sign up to set email alerts
|

SnowedOut Atlanta: Examining digital emergence on facebook during a crisis

Abstract: Individuals in emergencies form spontaneous, emergent groups to respond and recover. With the rise of social media use in crises, academics and professionals must be aware of how groups digitally coordinate emergent response efforts. This paper examines digital emergence through the case of SnowedOut Atlanta, a Facebook group formed during the 2014 ice storms in Atlanta. The posts and actions of the group members are in line with those of traditional emergent groups. For example, group members shared informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Community response post-disaster has been studied intensely for more than a century. Since Prince's iconic study of the Halifax shipping disaster (1920), sociologists and scholars of crisis communication have demonstrated thoroughly that in the midst of disasters individuals tend to respond with prosocial behaviors of support and community care, often in emergent, spontaneous, unplanned efforts by individuals and groups (Pyle et al, 2019;Quarantelli & Dynes, 1977;Waldman et al, 2017). In line with this body of research, early studies of responses to the COVID-19 pandemic suggest that individuals, households, and communities are experiencing solidarity.…”
Section: Natural Disastersmentioning
confidence: 98%
“…Community response post-disaster has been studied intensely for more than a century. Since Prince's iconic study of the Halifax shipping disaster (1920), sociologists and scholars of crisis communication have demonstrated thoroughly that in the midst of disasters individuals tend to respond with prosocial behaviors of support and community care, often in emergent, spontaneous, unplanned efforts by individuals and groups (Pyle et al, 2019;Quarantelli & Dynes, 1977;Waldman et al, 2017). In line with this body of research, early studies of responses to the COVID-19 pandemic suggest that individuals, households, and communities are experiencing solidarity.…”
Section: Natural Disastersmentioning
confidence: 98%
“…Other events have shown that social media was used to allow people access to different types of support during the event [58], including Facebook posts that conveyed gratitude, concerns, and complaints. Additionally, emergent groups can self-mobilize via social media platforms to provide information of specific interest to emergency managers [58].…”
Section: Current Public Use Of Social Media For Disaster Responsementioning
confidence: 99%
“…• Motivations for social media usage during disasters can also differ. Examples include providing and obtaining necessary information needed to manage the situation [23]; sharing information with emergency managers, and providing access to support services [58].…”
Section: Potential Usementioning
confidence: 99%
See 2 more Smart Citations